"ROLE OF ALLOGENEIC TRANSPLANTATION IN MULTIPLE MYELOMA IN THE ERA OF NEW DRUGS" - Benedetto Bruno; Luisa Giaccone; Moreno Festuccia; Mario Boccadoro (Mediterranean Journal of Hematology and Infectious Diseases)
High-dose melphalan with autologous stem cell rescue has been regarded as the standard of care for patients with newly diagnosed myeloma up to the age of 65-70 years. The recent development of agents with potent anti-tumor activity such as thalidomide, lenalidomide and bortezomib has further improved overall survival and response rates. However, relapse is a continuous risk. Allografting is a potentially curative treatment for a subset of multiple myeloma patients for its well documented graft-vs-myeloma effects. However, its role has been hotly debated. Even though molecular remissions have been reported up to 50% after high-dose myeloablative conditionings, their applications, given the high toxicity, have been for long limited to younger relapsed/refractory patients. These limitations have greatly been reduced through the introduction of non-myeloablative/reduced-intensity conditionings. The introduction of new drugs, characterised by low risks of early mortality, indeed requires to define role and timing of an allograft to capture the subset of patients who may most benefit from graft-vs-myeloma effects. Ultimately, new drugs should not be viewed as mutually exclusive with an allograft. They may be employed to achieve profound cytoreduction before and enhance graft-versus-myeloma effects as consolidation/maintenance therapy after an allograft. However, this combination should be explored only in well-designed clinical trials.